Exploring local flexibility/rigidity in psychrophilic and mesophilic carbonic anhydrases - CHIURI, ROCCO; MAIORANO, GABRIELE; RIZZELLO, Antonia; DEL MERCATO, LORETTA LAUREANA; CINGOLANI, Roberto; RINALDI, Rosaria; MAFFIA, Michele; POMPA, Pier Paolo (Biophysical Journal, 2009)
Molecular flexibility and rigidity are required to determine the function and specificity of protein molecules. Some psychrophilic enzymes demonstrate a higher catalytic efficiency at low temperatures, compared to the efficiency demonstrated by their meso/thermophilic homologous. The emerging picture suggests that such enzymes have an improved flexibility of the structural catalytic components, whereas other protein regions far from functional sites may be even more rigid than those of their mesophilic counterparts. To gain a deeper insight in the analysis of the activity-flexibility/rigidity relationship in protein structure, psychrophilic carbonic anhydrase of the Antarctic teleost Chionodraco hamatus has been compared with carbonic anhydrase II of Bos taurus through fluorescence studies, three-dimensional modeling, and activity analyses. Data demonstrated that the coldadapted enzyme exhibits an increased catalytic efficiency at low and moderate temperatures and, more interestingly, a local flexibility in the region that controls the correct folding of the catalytic architecture, as well as a rigidity in the hydrophobic core. The opposite result was observed in the mesophilic counterpart. These results suggest a clear relationship between the activity and the presence of flexible and rigid protein substructures that may be useful in rational molecular and drug design of a class of enzymes playing a key role in pathologic processes.